2005
DOI: 10.1111/j.1523-5378.2005.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori‐Specific Genes in the Oral Yeast

Abstract: The presence of H. pylori inside the yeast was indicated by light microscopy and PCR. It appears that yeasts, which are abundant in nature and thrive the mucosal surfaces of human, might serve as reservoirs and vehicles of H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 23 publications
(23 reference statements)
4
52
0
3
Order By: Relevance
“…42 Furthermore, it has been recently shown that H. pylori may be incorporated into the cells of yeast in oral cavity and transmitted to the stomach in yeast cells serving as carriers or H. pylori vectors to infect gastric mucosa but this requires further studies. 43 The next aspect we wanted to elucidate was if the triple therapy is successful in H. pylori eradication from the oral cavity as and from the stomach. We clearly observed that 1-week triple therapy worked quite well for gastric H. pylori eradication and additionally attenuated the dyspeptic symptoms and reduced significantly antiCagA antibodies in blood, but was neither fully successful in eradicating H. pylori from oral cavity nor in decreasing the titer of anti-H. pylori antibodies in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…42 Furthermore, it has been recently shown that H. pylori may be incorporated into the cells of yeast in oral cavity and transmitted to the stomach in yeast cells serving as carriers or H. pylori vectors to infect gastric mucosa but this requires further studies. 43 The next aspect we wanted to elucidate was if the triple therapy is successful in H. pylori eradication from the oral cavity as and from the stomach. We clearly observed that 1-week triple therapy worked quite well for gastric H. pylori eradication and additionally attenuated the dyspeptic symptoms and reduced significantly antiCagA antibodies in blood, but was neither fully successful in eradicating H. pylori from oral cavity nor in decreasing the titer of anti-H. pylori antibodies in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…É universalmente aceito que a bactéria apenas consiga alcançar a mucosa gástrica através da boca, pois se trata de um microorganismo não invasivo, que parece ser transmitido de pessoa a pessoa de forma direta ou indireta 11 . As principais rotas de transmissão são oral-oral, fecaloral e gastro-oral, pois antígenos da bactéria têm sido detectados na cavidade oral 32 , eliminados através das fezes 27 , como também em conteúdos de vômitos 21 . A concordância de tipos moleculares desta bactéria, entre indivíduos da mesma família, indica que a transmissão ocorre entre seus membros 11 12 17 32 .…”
unclassified
“…49 , presenta la primera evidencia de crecimiento de H. pylori en agua potable municipal, esto gracias al desarrollo de un medio selectivo, llamado agar modificado urea Columbia (MCUA) 50 . Diversos autores 51,52 discuten la importancia de desarrollar nuevas técnicas para la detección, aislamiento y cultivo de bajos recuentos de H. pylori en placa bacteriana oral. De acuerdo a nuestros resultados, creemos que este problema ha sido parcialmente superado, pues es posible detectar el ADN de la bacteria, aunque no se logre su aislamiento.…”
Section: Discussionunclassified